International criminal judiciary as a means to keep and protect peace and international security - Jovašević Dragan (Međunarodni Problemi)
After a long historical development, the second half of the 20th century has inaugurated the new, latest branch of the punitive law - international criminal law. By its legal nature and characteristics it is somewhere between the national criminal law and international public law, maintaining its peculiarity and independence. The basic and most important notion and institute of this branch of law is certainly the international criminal act. In the theory of law (domestic and foreign), there are several views on the notion and contents of the international criminal act. However, it can be concluded that this notion implies a socially dangerous, illegal act committed by the perpetrator and defined as a criminal act whose perpetrator is to be punished as prescribed by the law. Such a defined notion of the international criminal act includes its basic elements, and these are as follows: 1) the act of a man (including the act of an adult person that can be committed in three forms: acting, non-acting, failure to provide proper supervision, effect and casualty; 2) social danger; 3) unlawfulness; 4) definition of an act by rules, and 5) guilt of the perpetrator. There are two kinds of international criminal acts: international criminal acts in a narrow sense and international criminal acts in a broad sense. The most significant are certainly the international criminal acts in a narrow sense that are directed towards violation or endangering of the universal, general civilisation values - international law and humanity - what is actually the subject of protection from these criminal acts. Apart from the international criminal act, the theory of law also includes a foreign criminal act (any criminal act with a foreign element). By all this, these two notions coincide largely, but are also considerably different from each other. Apart from the general notion of the international criminal act, the theory of law also includes a special being or a special notion of the international criminal act by whose characteristics and specific forms and shapes of manifestation some international criminal acts or responsibility of their perpetrators actually differ from each other. As a matter of fact, all international legal documents in this field (and then national criminal legislation as well) deal with the whole system of various incriminations punished by various kinds and sorts of penalties (as basic sorts of criminal sanctions). The following documents deal with some international criminal acts in their specific forms and shapes of manifestation: The Statute of the International Military Tribunal (that served to reach the Nuremberg and then the Tokyo verdicts), the Law No. 10 of the Control Council for Germany, the Statute of the Hague Tribunal for the Former Yugoslavia as well as the statutes of some other ad hoc tribunals such as: Tribunals for Rwanda, Eastern Timor and Sierra Leone, then the Statute of the Iraqi Special Tribunal and finally the Permanent International Criminal Court Statute (the so-called Rome Statute).